COMPARATIVE INCOME ANALYSIS OF RICE FARMING (Oryza sativa L.) USING CERTIFIED AND NON-CERTIFIED CIHERANG SEED VARIETIES - Rudianoor Rudianoor; Ana Zuraida; Inda Ilma Ifada (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
This study evaluates the financial performance of Ciherang rice farming using certified and non-certified seeds in Ulu Benteng, Marabahan Subdistrict. Cultivation follows standard agronomic practices such as seedbed preparation, planting (tegel system), fertilization, and harvesting. Certified seed farming incurs explicit and implicit costs of IDR 4,924,024 and IDR 4,221,471 respectively, yielding revenue of IDR 15,026,477, with income of IDR 10,102,465 and profit of IDR 5,880,976. In contrast, non-certified seed farming incurs slightly lower costs (IDR 4,567,240 and IDR 4,098,846), but generates lower revenue (IDR 12,577,846), income (IDR 7,748,308), and profit (IDR 3,911,760). The profit gap of IDR 1,969,216 confirms that certified seeds deliver better financial outcomes, supporting their use to enhance farm profitability and sustainability.